IMPLEMENTASI MBKM KEWIRAUSAHAAN : PELATIHAN PEMANFAATAN BUAH LERAK MENJADI DETERJEN CAIR TANPA BAHAN KIMIA DI BINUS - Koerniawan Hidajat; Desti Nurul Fitria (Jurnal Abdimas Bina Bangsa, 2023)
Lerak or commonly called soapberry or soapnut is a fruit that looks like a walnut and grows on a tree as high as 10 meters. This fruit is known for the properties of its seeds which are used as a traditional detergent. This skin seed contains saponins which produce foam and can function as a detergent for washing textiles in ancient times, but it can also be used to wash clothes with only certain fabrics. The socialization aims to increase the knowledge of housewives in the Pinang Rant area about leather axes and the use of natural ecological soap. The implementation method is to socialize lerak seeds and use them as an ecological detergent for cloth or clothing. The results of this socialization for housewives can be seen from the target material presented, and housewives in the Pinang Ranti area can master the material presented and directly use this lerak detergent to wash clothes